Tindak Pidana Pencurian Anak Terkait dengan Undang-Undang Nomor 11 Tahun 2012 Tentang Sistem Peradilan Anak : Studi Kasus Putusan Nomor : 9/PID SUS.A/2019/PN.BKL - Erva Yunita; Handar Subhandi Bakhtiar (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The author in writing raised the case on Decision Number: 9/Pid.Sus.A/2019/PN.Bkl, where the defendant Ropik Bin Sukkur was found guilty of committing the crime of theft of a blue and white Beat motorcycle for his actions, the defendant was sentenced to 3 (three) years. three) months and did not get a diversion attempt. For this reason, the author will examine how the criminal imposition of criminal acts of theft of article 363 of the Criminal Code committed by minors in terms of Law Number 11 of 2012 concerning the Juvenile Criminal Justice System and how the judge's considerations in imposing a crime against the perpetrators of the crime of theft of article 363 of the Criminal Code in terms of the perspective of restorative justice, the research method used in this author is the normative juridical method of library law research carried out by researching library materials or secondary data, sentencing refers to the theory of relative punishment where the purpose of sentencing is as a means of improvement for the accused. itself, while the judge's considerations refer to two aspects, namely juridical and non-juridical aspects, juridical aspects refer to Article 362 of the Criminal Code and noin juridical refers to mitigating and aggravating matters.